Menuju Keemasan Pariwisata Sejarah Lokal: Revitalisasi Makam Seniman Giri Sapto oleh Masyarakat Pajimatan - Belinda Feronica (Jurnal Abdimas Pariwisata, 2025)
Towards the Golden Era of Local Heritage Tourism: Community-Led Revitalization of Giri Sapto Artist Cemetery in Pajimatan. The Giri Sapto Artist Cemetery, located on Bukit Gajah, Girirejo, Imogiri, Bantul, Yogyakarta, is a burial site dedicated to artists and cultural figures. Established on February 6, 1988, it is managed by the Giri Sapto Artist and Cultural Heritage Foundation. A site survey revealed that the local community has strong potential to revive tourism in the area, especially with the construction of a museum near the entrance. This study recommends collaborative revitalization efforts among key stakeholders, including the Bantul Tourism Office, Imogiri Subdistrict Government, and Wukirsari Village Administration. Community involvement is essential in developing a new tourism package under the concept of Desa Wisata Ziarah Imogiri (Imogiri Pilgrimage Tourism Village). The proposed route starts from the still-active Imogiri Royal Cemetery, followed by a cultural exploration of Pajimatan Hamlet, and continues to Giri Sapto as an artistic pilgrimage destination. The active participation of locals reflects their readiness to reawaken tourism potential in response to the evolving tourism landscape in Bantul.